Positive charge transport in an alternating oligo-p-phenylenevinylene-derivative/aliphatic-segment block copolymer - Benvenho,A.R.V. (2001)
An effective positive charge carrier mobility of 4.4 x 10 -9 cm²/V.s was directly determined using analytical expressions for space-charge-limited current in poly(1,10-decanedioxy-2-methoxy-1,4-phenylene-1,2-ethenylene-3,6-dimethoxy- 1,4-phenylene-1,2-ethenylene-3-methoxy-1,4-phenylene), OPPVDBC, which is a soluble electroluminescent alternating block copolymer. Current vs. voltage measurements have been made using single carrier injection and transport in metal/OPPVDBC/metal structures. The experimental results demonstrate that the positive charge transport in these devices is space-charge-limited and temperature dependent. Additionally, there is evidence that the evaporation of the aluminum electrode induces an increase in the charge density near the Al/OPPVDBC interface.